The imagined future and the restitucion of the Inca Dominion of Garcilaso de la Vega - Maticorena Estrada, Miguel (2009)
We try to link two concepts. One, the future of a community or cultural nation. The other is the restitucion as a political project. One hypothesis: the Restitucion, we believe that cha- llenges to conquer. Garcilaso accepts only the Providentialism and calls this future «coming days». As is History could not dispense with the future. This becomes the Restitution in the